Effect of method of caries induction on aged resin-dentin bond of primary teeth - Lenzi, Tathiane Larissa; Calvo, Ana Flávia Bissoto; Tedesco, Tamara Kerber; Ricci, Hérica Adad [UNESP]; Hebling, Josimeri [UNESP]; Raggio, Daniela Prócida (Biomed Central Ltd, 2015)
Background: To investigate the influence of chemical and microbiological methods of caries induction on bond degradation of adhesive systems to primary dentin.Methods: Flat dentin surfaces from 36 primary molars were assigned to three groups (n = 12) according to method to induce caries-affected dentin: (1) control (sound dentin); (2) pH-cycling; and (3) microbiological caries induction model. Teeth were submitted to caries induction for 14 days for both methods, and the sound dentin was stored in distilled water during the same period. Specimens from each experimental group were then randomly reassigned to two subgroups (n = 6) according to the adhesive system tested: two-step etch-and-rinse adhesive (Adper Single Bond 2 - SB) or two-step self-etch system (Clearfil SE Bond - CSEB). Composite buildups were constructed and sectioned to obtain bonded sticks to be subjected to microtensile (mu TBS) testing immediately or after 12 months of water aging. The mu TBS means were analyzed by three-way repeated measures ANOVA and Tukey's tests (alpha = 0.05).Results: The mu TBS values obtained to artificially-created caries-affected dentin were lower compared with sound dentin, but were not affected by method of caries induction. Water storage for 12 months reduced bond strengths, except to CSEB bonded to sound dentin.Conclusion: Chemical and microbiological methods affect similarly the stability of resin-dentin bonds in primary teeth.
Keywords: Caries-affected dentin; Artificial caries; pH-cycling; Microbiology; Longevity